Digital transformation in journalism: mini review on the impact of AI on journalistic practices - Sonni, Alem Febri (Frontiers in Communication, 2025)
This mini-review examines the digital transformation in journalism over the past decade (2014–2024), focusing on adopting AI technologies, changing business models, and evolving professional practices. Through an analysis of recent literature, we identify three main streams of research: technology integration in newsrooms, shifting content consumption patterns, and business model innovation. Findings show that AI has changed how news is produced and distributed but poses significant ethical and professional challenges. Current research gaps include a limited understanding of the long-term impact of AI on journalistic practice, insufficient cross-cultural studies of digital adoption patterns, and early explorations of the effectiveness of immersive journalism. This review suggests future research directions in the ethics of automated journalism, sustainable digital business models, and cross-platform content optimization strategies.